AN ANALYSIS OF SLANG WORDS IN THE LYRICS OF FAR EAST MOVEMENT SONG AS THE FORM OF LANGUAGE DEVELOPMENT AND IT’S USED IN THE DAILY LIFE - Vonny Elisa Oktavia (Proceedings Education and Language International Conference, 2017)
Language is the most important instrument for humans to make a communication. Along with the development of the era, language also changes and has many varieties. There are many varieties of language development used in the daily life. One of the varieties of language is slang words. Slang word means nonstandard words made by the modern community and usually used by young people in certain condition. Slang word often found in the daily conversation or literary work like movie, novel, even song. This study will discuss about slang word that found in literary work especially in the song. Since song is one of the literary work that can influence the use of language in the daily life. In this case, this paper would analyze slang word found in the lyrics of Far East Movement Songs using Sociolinguistic approach. Also how the song affect in the use of slang word in the daily life. This study uses descriptive qualitative method. The data collected from the lyrics of Far East Movement songs from Internet. This study tries to find and identify the slang word and analyze the characteristic of slang word uses in the lyrics of Far East Movement songs.Keywords: language development, slang, song, Far East Movement, lyrics, sociolinguistic